Pengaruh Ritel Mix terhadap Gaya Hidup Mahasiswa - Saleha, Dinda Tania; Pujianto, Agung; Tjahjono, Endro (Jurnal Dinamika Administrasi Bisnis, 2017)
This study entitled "Effect of Retail Mix the Lifestyle Students (Case Study Angkringan" Mbah Clark "in Jl. Prapen Surabaya)". This study aims to determine the Retail Mix is there any influence on the lifestyle of students and the truth variable atmosphere of Retail Mix dominant influence on the lifestyle of students. The population in this study were all students in the city of Surabaya ever visit or hang out in Angkringan Mbah Cokro Surabaya.         Collecting data using questionnaires with sampling techniques nonprobability Sampling Sampling is incidental that the number of respondents 75 people. Data analysis method used is multiple linear regression analysis were processed with the help of SPSS applications. The variables used were Retail Mix consisting of food, service, and atmosphere as the independent variable and Lifestyle as the dependent variable.In conclusion, as follows: (1) Partially food is not positive and significant impact on the lifestyle that showed with b1 = 0.237, t = 1.569, and sig. 0.121. (2) Partially atmosphere is not positive and significant impact on the lifestyle indicated by the value b2 = 0.309, t = 1.902, and sig. 0.061. (3) Partially servicing positive and significant impact on the lifestyle that showed with b3 = 0.268, t = 2.106 and sig. 0,039 and. (4) the food, atmosphere and service simultaneously positive and significant influence on purchasing decisions that are indicated by the value of F = 14.451, sig. 0,000, and the value of Adjusted R2 of 0.353. This means that 35.5% lifestyle described by the food, atmosphere and service, while 64.5% is explained by other variables not examined in this study. Keywords: food, atmosphere, service, Lifestyle